Understanding PFOS Adsorption on a Pt Electrode for Electrochemical Sensing Applications. Issue 2 (27th December 2022) - Gogoi, Pratahdeep; Yao, Yu; Li, Yuguang C.
Abstract: Per‐ and polyfluroalkyl substances (PFAS) are drawing increasing attention in the research community due to their wide spread applications and their toxicity to animals and humans. Effective early detection method of PFAS chemicals in aqueous environment is important to reduce exposure and mitigate the potential toxic effects. This study focuses on the electrochemical detection of per‐fluoro octane sulfonate (PFOS) with differential pulse voltammetry and electrochemical impedance spectroscopy on a bare platinum electrode. We observe three distinct regions of adsorption behaviors with respect to PFOS concentration from 0–1000 nM, reflecting changes in the modes of adsorption due to different adsorbate‐adsorbate interactions on a bare electrode. The adsorption isotherm constant for PFOS adsorption on a Pt electrode is calculated to be 1.6×10 12  cm 3  mol −1 from fitting the electrochemical data with a modified Langmuir isotherm model. Abstract : Electrochemical Detection of Per‐Fluoro Octane Sulfonate : The adsorption dynamic of PFOS molecule on a metal electrode depends on its concentration – at low concentration, random orientation of adsorption is observed; at medium concentration, PFOS molecule is aligned due to adsorbate‐adsorbate interaction. At high concentration, multiplayers of PFOS is adsorbed on a metal surface.